Distribution of Peptidyl-Prolyl Isomerase (PPIase) in the Archaea - Anchal,; Kaushik, Vineeta; Goel, Manisha (Frontiers in Microbiology, 2021)
Cis-trans isomerization of the peptide bond prior to proline is an intrinsically slow process but plays an essential role in protein folding. In-vivo cis-trans isomerization reaction is catalyzed by Peptidyl-prolyl isomerase (PPIases), a category of proteins widely distributed among all the three domains of life. The present study is majorly focused on the distribution of different types of PPIases in the archaeal domain. All the three hitherto known families of PPIases (namely FKBP, Cyclophilins and parvulins) were studied to identify the evolutionary conservation across the phylum archaea. The basic function of cyclophilin, FKBP and parvulin has been conserved whereas the sequence alignment suggested variations in each clade. The conserved residues within the predicted motif of each family are unique. The available protein structures of different PPIase across various domains were aligned to ascertain the structural variation in the catalytic site. The structural alignment of native PPIase proteins among various groups suggested that the apo-protein may have variable conformations but when bound to their specific inhibitors, they attain similar active site configuration. This is the first study of its kind which explores the distribution of archaeal PPIases, along with detailed structural and functional analysis of each type of PPIase found in archaea.